2016
DOI: 10.12659/ajcr.896989
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy in Neuroendocrine Bladder Cancer: A Case Report

Abstract: Patient: Male, 71Final Diagnosis: Neuroendocrine cancer bladderSymptoms: Dysuria • haematuriaMedication: —Clinical Procedure: Transurethral resection of the bladder tumorSpecialty: OncologyObjective:Rare diseaseBackground:Small cell carcinoma of the urinary bladder is a rare and aggressive form of bladder cancer that mainly presents at an advanced stage. As a result of its rarity, it has been described in many case reports and reviews but few retrospective and prospective trials, showing there is no standard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Based on available literature [ 3 , 8 , [14] , [15] , [16] , [17] , [18] , [19] , [20] ], three case reports state a mass in the urinary bladder with bladder stone has the biopsy with the squamous cell carcinoma [ 3 , 8 , 16 ], while others reported translational cell carcinoma, urothelial carcinoma, hemangioma, and villous adenoma. By diameter, the stones found in our patient's bladder are perhaps the largest which ever reported being associated with bladder SCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on available literature [ 3 , 8 , [14] , [15] , [16] , [17] , [18] , [19] , [20] ], three case reports state a mass in the urinary bladder with bladder stone has the biopsy with the squamous cell carcinoma [ 3 , 8 , 16 ], while others reported translational cell carcinoma, urothelial carcinoma, hemangioma, and villous adenoma. By diameter, the stones found in our patient's bladder are perhaps the largest which ever reported being associated with bladder SCC.…”
Section: Discussionmentioning
confidence: 99%
“… KUB: large, lamellated radiopaque shadow at the pelvis; VCUG revealed left reflux grade IV; Cystoscopy: stone with underlying multiple erythematous bladder wall; Radical cystectomy + ileal conduit urinary diversion was conducted Kirakoya et al [ 3 ] 2018 60 M Dysuria; haematuria; nocturia, intermittent suprapubic pain; a hard well-defined suprapubic mass; digital rectal examination: a hard and painless mass Pyuria; plain abdominal x-ray: opacity occupying the entire pelvic. Whitish weighed 1.1 kg with 13 cm × 10 cm Yes Muscle invasive squamous cell carcinoma (SCC) NA NA lost to follow up for 18 months; recurrent haematuria; died from severe anaemi Cystolithotomy The patient refuses radical cystectomy Prelaj et al [ 17 ] 2016 71 M Dysuria; haematuria, Cystectomy + lymphadenectomy + placement of bilateral ureterocutaneostomy; No Yes pT2 high-grade urothelial carcinoma Yes NA Underwent neoadjuvant chemotherapy On the left lateral, the anterior wall was found bladder vegetative lesion with size of 34 × 24 mm Syu, Syuan-hao et al [ 18 ] 2018 17 F persistent gross hematuria Partial resection of TURBT showed chronic inflammation; 3.6 cm mass on supero-anterior wall of bladder No Yes Cavernous hemangioma NA NA Showed no local recurrence in 2 years (6, 12, and 24 months follow up) on Cystoscopy and CT Morozumi et al [ 19 ] 2017 ...…”
Section: Discussionmentioning
confidence: 99%
“…Whether used alone or as part of a multimodal regimen, from cytostatics cisplatin (or possibly carboplatin) and etoposide, ifosfamide-doxorubicin, cisplatin (or carboplatin) and irinotecan are recommended, and in mixed tumours, methotrexate, vincristine, cyclophosphamide and taxanes may be added. The poor general condition of the patient sometimes only allows monotherapy [5,8,11,13,16,17,21,[25][26][27][28][29].…”
Section: Cytostatic Treatmentmentioning
confidence: 99%
“…Early diagnosis of the disease as well as surgery, neoadjuvant, adjuvant, or palliative chemotherapy with or without radiotherapy are the cornerstones of patient care (13,(48)(49)(50). Details about prognosis and therapy are shown in Table III (13,23,35,41,42,44,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Neuroendocrine Tumors Of the Urinary Bladdermentioning
confidence: 99%